Use of Arthrobacter davidanieli as a live vaccine against Renibacterium salmoninarum and Piscirickettsia salmonis in salmonids - Salonius, K; Siderakis, C; MacKinnon, A M; Griffiths, S G (Developments in biologicals, 2005)
Arthrobacter davidanieli (proposed species nomenclature) is a non-pathogenic Gram-variable bacterium related to, but taxonomically distinct from, Renibacterium salmoninarum, the aetiological agent of bacterial kidney disease (BKD). We have demonstrated that vaccination with live A. davidanieli is effective against BKD in Atlantic salmon (Salmo salar) showing above 80 relative percent survival in experimental challenge trials. Good protection was also demonstrated in long-term field trials where Atlantic salmon were naturally exposed to R. salmoninarum challenge until 23 months after vaccination. The same vaccine, which is licensed in Canada against BKD has also proved effective in reducing mortality from experimental challenge of coho salmon (Oncorhynchus kisutch) with Piscirickettsia salmonis, the causative agent of piscirickettsiosis. Under field conditions in Chile, use of the vaccine led to a significant reduction in piscirickettsiosis mortality in coho salmon over 10 months following sea transfer. The vaccine strain is unique in that it is the first live organism to be licensed as a vaccine for use in aquaculture. Potential mechanisms of protection against the two taxonomically disparate pathogens are discussed.